1992
DOI: 10.2165/00003088-199222010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interactions with Rifampicin

Abstract: Rifampicin, an antituberculosis drug, is usually administered for 4 to 12 months with other antituberculosis drugs or medications from other classes. A potential for drug interactions often exists because rifampicin is a potent inducer of hepatic drug metabolism, as evidenced by a proliferation of smooth endoplasmic reticulum and an increase in the cytochrome P450 content in the liver. The induction is a highly selective process and not every drug metabolised via oxidation is affected. Case reports and studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
67
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 110 publications
3
67
1
1
Order By: Relevance
“…Induction of CYP results in increased elimination of co-administered drugs, whose metabolism is mediated by the same isozymes, and this is often related to the insufficient pharmacological effects. There have been some reports showing such unexpected interactions by RF with clinically important drugs including cyclosporine, nifedipine, oral contraceptives, phenytoin, and theophylline (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of CYP results in increased elimination of co-administered drugs, whose metabolism is mediated by the same isozymes, and this is often related to the insufficient pharmacological effects. There have been some reports showing such unexpected interactions by RF with clinically important drugs including cyclosporine, nifedipine, oral contraceptives, phenytoin, and theophylline (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…3) In addition, rifampicin and its analogue rifabutin increase their own metabolism after repeated administration to patients. 4) Rifampicin also causes an increase in the urinary ratio of 6b hydroxycortisol to 17 hydroxycorticosterone, indicating the induction of CYP3A4 in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Quinine is widely used to treat malaria in endemic phylline, antipyrine, hexobarbitone and cyclosporine malaria areas where Plasmodium falciparum is resist- [2][3][4][5][6][7][8]. It has been shown that rifampicin decreases the ant to chloroquine.…”
Section: Introductionmentioning
confidence: 99%
“…drug metabolism in humans [1,2] and is known to Isoniazid, another anti-tuberculosis drug, inhibits interact with a number of drugs such as warfarin, hepatic oxidative metabolism of a number of drugs digitoxin, dapsone, chlorpropamide, metoprolol, theosuch as phenytoin (metabolised by CYP2C9), carba- [3,[14][15][16]. This suggests that inhibition of oxidative drug metabolism by isoniazid is not selective [17].…”
Section: Introductionmentioning
confidence: 99%